Legalitas Bank Sperma (Sperm Bank) di Indonesia - Putri, Lutfiya Hendra Setianing; Latumahina, Rosalinda Elsina (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The existence of sperm finance transactions and its legal ramifications under Indonesian law are examined in this paper, particularly in light of the passage of Law Number 17 of 2023 concerning Health. This study uses normative legal research instruments and a legislative and conceptual methodology to examine sperm compliance banking practices with national legal provisions and the moral, religious, and social principles of Indonesian society. The results show of assisted reproductive technology (ART), these services are only permitted for legally married couples. The use of sperm donors or third-party sperm banking services is not legally recognized due to the potential for uncertainty regarding. To date, there are no regulations explicitly governing the operation of sperm banking, making the practice illegal and risky for health facilities and medical personnel. This legal vacuum demands more specific regulations through government regulations or ministerial regulations that govern procedures, oversight, and everyone's legal protection. This study highlights how crucial balance is medical innovation, reproductive rights protection, and the moral values of Indonesian society.